Course and Predictors of Adult Spinal Sagittal Disorders: A 10-Year Prospective Case Series - Mannström, Heidi; Multanen, Juhani; Ylinen, Jari; Hautala, Arto; Peuna, Arttu; Karttunen, Lauri; Pekkanen, Liisa; Kyrölä, Kati (Spine (Philadelphia, Pa. 1976), 2025)
Prospective case series. To study the natural course of adult spinal deformity (ASD) over a 10-year period and the determinants associated with postural malalignments. ASD comprises a heterogeneous spectrum of abnormalities of the thoracolumbar spine throughout adulthood. Radiographic deterioration of sagittal alignment is a combination of decreased lumbar lordosis (LL), PI-related retroversion of the pelvic tilt (PT), anteriorizing sagittal vertical axis (SVA), and increased T1 pelvic angle (TPA). The full spine radiographs were taken to measure the SRS-Schwab sagittal modifiers PI-LL, PT, and SVA to measure the possible change in severity of deformity from the 204 volunteer participants (mean age 62.7 yr, 61% female), which were 32% of the 637 consecutive patients with prolonged back pain who originally joined the study in 2012-2013. Each participant completed the Scoliosis Research Society 22r (SRS-22r) questionnaire. The mean change in the SRS-Schwab score was 0.4 units (baseline 1.1 vs . follow-up 1.5, P <0.001) implying deterioration of the spinal deformity. The SRS-Schwab score decreased (n=76, 37%), remained the same (n=102, 50%), or improved (n=26, 13%). Four predictive factors for a change of sagittal alignment were found, of which the poor score in the SRS-22r function domain ( P =0.049) and severe pelvic tilt (PT greater than 30°, P =0.006) predicted the change. This study showed the variability in how sagittal alignment of the spine changes during the 10-year follow-up period. The ASD patients with poor self-assessed functional ability and disturbed pelvic position were associated with the risk of deterioration in spinopelvic alignment. The diversity in the natural course of ASD and the known risk factors highlight the need for tailored advice when planning preventive treatment procedures for ASD patients. Level III.